1994
DOI: 10.1021/es00061a024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition and State of Organic Components on Polycyclic Aromatic Hydrocarbon Decay in Atmospheric Aerosols

Abstract: Photodegradation of six polycyclic aromatic hydrocarbons (PAHs) was studied in liquids composed of actual organic aerosol constituents using a photochemical turntable reactor. All six PAHs exhibited more rapid decay in a liquid mixture of methoxyphenols, an abundant class of compounds present in wood smoke, than in hexadecane, which is representative of aliphatic hydrocarbons abundant in diesel soot and automobile exhaust. The most rapid decay was observed for benz [a] anthracene and benzo[a]pyrene in both hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 29 publications
5
87
1
Order By: Relevance
“…These particles can be generally described as either nonporous and covered by an organic film (Husar and Shu 1975;Gill et al 1983) or porous (Ancelet et al 2011). Considering mounting evidence of the presence of liquid-like organic matter in the particles (Bidleman et al 1986;Japar et al 1984;McDow et al 1994), the porous particles are reasonably expected to have their pores filled with such organic matter. Summarizing the morphology observation and model description of airborne particles in the literatures, we think that the four morphologies displayed in Figure 1b-e is representative of those typically encountered in the case of particles with organic constituents.…”
Section: Model Developmentmentioning
confidence: 99%
“…These particles can be generally described as either nonporous and covered by an organic film (Husar and Shu 1975;Gill et al 1983) or porous (Ancelet et al 2011). Considering mounting evidence of the presence of liquid-like organic matter in the particles (Bidleman et al 1986;Japar et al 1984;McDow et al 1994), the porous particles are reasonably expected to have their pores filled with such organic matter. Summarizing the morphology observation and model description of airborne particles in the literatures, we think that the four morphologies displayed in Figure 1b-e is representative of those typically encountered in the case of particles with organic constituents.…”
Section: Model Developmentmentioning
confidence: 99%
“…4 Air particulates of PAH are degraded under atmospheric conditions such as, strong sunlight, high temperatures and air humidity, and elevated concentrations of ozone and nitrogen oxides. 5 Several studies have been carried out with this class of compounds 1005 Toledo et al Vol. 18, No.…”
Section: Introductionmentioning
confidence: 99%
“…17 Other polyaromatic hydrocarbon degradation studies have shown a more rapid decay in a liquid mixture of methoxyphenols, an abundant class of compounds present in wood smoke, compared with hexadecane, which is representative of aliphatic hydrocarbons abundant in diesel soot and automobile exhaust. 18 Particleassociated PAHs from wood smoke have also been shown to decay rapidly in sunlight under some atmospheric conditions. Their reactivity is strongly influenced by solar radiation intensity, temperature, and atmospheric concentrations of water, ozone, and nitrogen oxides.…”
Section: Resultsmentioning
confidence: 99%